In rabbits with cheyletiellosis is topical selamectin or injectable ivermectin a more effective treatment? - Mouëzy, Juliette (Veterinary Evidence, 2022)
PICO question In rabbits with cheyletiellosis is topical selamectin or injectable ivermectin a more effective treatment? Clinical bottom line Category of research Treatment. Number and type of study designs reviewed One paper directly answered the PICO question, a retrospective clinical design study, and was critically reviewed. Strength of evidence. Strong. Outcomes reported Both topical selamectin and injectable ivermectin are safe and effective in treating cheyletiellosis. There is no significant difference in the effectiveness of both drugs in treating the infestation. Conclusion In pet rabbits with Cheyletiella parasitivorax infestations both topical selamectin and injectable ivermectin have been recognised to be a safe and effective treatment. There is currently insufficient evidence that one is more effective than the other and therefore veterinarians should consider their own clinical experience, client preference and use the licensed product first (in the UK, ivermectin (Xeno, Dechra) spot-on). However, this Knowledge Summary does not comment on the effectiveness of topical ivermectin in treating cheyletiellosis. If injectable ivermectin is , topical selamectin can be used under the cascade as an alternative treatment, as it is licensed for the same indication in dogs and cats. How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.